Genetic variability in E6, E7 and L1 genes of Human Papillomavirus 62 and its prevalence in Mexico - Artaza-Irigaray, Cristina; Olszewski, Dominik (Infectious agents and cancer, 2017)
BACKGROUND: Human papillomavirus (HPV) is the main etiological agent of cervical cancer, the third most common cancer among women globally and the second most frequent in Mexico. Persistent infection with high-risk HPV genotypes is associated with premalignant lesions and cervical cancer development. HPVs considered as low risk or not yet classified, are often found in coinfection with different HPV genotypes. Indeed, HPV62 is one of the most prevalent HPV detected in some countries, but there is limited information about its prevalence in other regions and there are no HPV62 variants currently described. The aim of this study was to determine the prevalence of HPV62 in cervical samples from Mexican women and to identify mutations in the L1, E6 and E7 genes, which have never been reported in our population. METHODS: HPV screening was performed by Cobas HPV Test in women who attended prevention health programs and dysplasia clinics. All HPV positive samples (n = 491) and 87 additional cervical cancer samples were then genotyped with Linear Array HPV Genotyping test. Some samples were selected to corroborate genotyping by Next-Generation sequencing. On the other hand, nucleotide changes in L1, E6 and E7 genes were determined using PCR, Sanger sequencing and analysis with the CLC-MainWorkbench 7.6.1 software. L1 protein structure was predicted with the I-TASSER server. RESULTS: Using Linear Array, HPV62 prevalence was 7.6% in general population, 8% in Cervical Intraepithelial Neoplasia grade 1 (CIN1) samples and 4.6% in cervical samples. The presence of HPV62 was confirmed with Next-Generation sequencing. Regarding L1 gene, novel sequence variations were detected, but they did not alter the tertiary structure of the protein. Moreover, several nucleotide substitutions were found in E6 and E7 genes compared to reference HPV62 genomic sequence. Specifically, three non-synonymous sequence variations were detected, two in E6 and one in E7. CONCLUSIONS: HPV62 is a frequent HPV genotype found mainly in general population and in women with CIN1, and in 90.5% of the cases it was found in coinfection with other HPVs. Novel nucleotide changes in its L1, E6 and E7 genes were detected, some of them lead to changes in the protein sequence.